2022
DOI: 10.18196/jrc.v3i4.14759
|View full text |Cite
|
Sign up to set email alerts
|

A New 4-DOF Robot for Rehabilitation of Knee and Ankle-Foot Complex: Simulation and Experiment

Abstract: Stationary robotic trainers are lower limb rehab robots which often incorporate an exoskeleton attached to a stationary base. The aim is to recover range of motion, increase muscles strength and reduce joint stiffness. The issue observed in the stationery trainers which involve knee and ankle-foot complex joints simultaneously is that they restrict the natural motion of ankle-foot in rehab trainings due to the insufficient Degrees of Freedom (DOFs) of these trainers. This restriction makes the joints deviate f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Moreover, in a bi-articular knee–ankle–foot exoskeleton, BF muscle activity was lower than in the powered-off condition corresponding to the assistance of knee flexion and reducing the person’s metabolic cost of walking [ 46 ]. In the case of pathological patients, therapists require them to move all joints during specific therapies, where it has been shown that training involving several joints simultaneously generates a greater physiological condition [ 47 ]. This indicates that, by assisting more joints, the performance of the two devices improves by reducing the activity of most of the muscles evaluated, which means complete assistance to the hip and knee flexion/extension movements allowing a passive degree of hip adduction/abduction and, in addition, providing dorsi-plantarflexion of the ankle with a soft mechanism that permits greater degrees of freedom in this joint.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a bi-articular knee–ankle–foot exoskeleton, BF muscle activity was lower than in the powered-off condition corresponding to the assistance of knee flexion and reducing the person’s metabolic cost of walking [ 46 ]. In the case of pathological patients, therapists require them to move all joints during specific therapies, where it has been shown that training involving several joints simultaneously generates a greater physiological condition [ 47 ]. This indicates that, by assisting more joints, the performance of the two devices improves by reducing the activity of most of the muscles evaluated, which means complete assistance to the hip and knee flexion/extension movements allowing a passive degree of hip adduction/abduction and, in addition, providing dorsi-plantarflexion of the ankle with a soft mechanism that permits greater degrees of freedom in this joint.…”
Section: Discussionmentioning
confidence: 99%
“…The Bridgestone Company produced the first commercial version of the pneumatic artificial muscle (PAM) [2]. It is used to construct soft robots with several bendable joints and a high degree of freedom, rather than rigid robots with discrete fixed joints [3][4][5][6][7]. These robots provide safer interactions with humans when directly in contact with their bodies [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%